Antifertility Effect of Bougainvillea spectabilis or Paper Flower - Ghogar, Anisa; Jiraungkoorskul, Wannee (Pharmacognosy Reviews)
Bougainvillea spectabilis (Family: Nyctaginaceae), commonly referred to as Great Bougainvillea or Paper Flower, is one of the traditional medicinal plants with potential antifertility activity. The aqueous extract and decoction of this plant have been used as fertility control among the tribal people in many countries. Furthermore, it has been shown to possess anticancer, antidiabetic, antihepatotoxic, anti‑inflammatory, antihyperlipidemic, antimicrobial, antioxidant, and antiulcer properties. Its phytoconstituents such as alkaloids, essential oils, flavonoids, glycosides, oxalates, phenolics, phlobotannins, quinones, saponins, tannins, and terpenoids were reported as the basis of its efficacious therapeutic properties. The other important constituents which contribute to the remedial properties are bougainvinones, pinitol, quercetagetin, quercetin, and terpinolene. Published information on the antifertility property of B. spectabilis was gathered by the use of different database platforms including Google Scholar, ScienceDirect, PubMed, SciFinder, and Scopus. These database platforms were used to provide an up‑to‑date review on its importance.
Keywords: Antifertility; Bougainvillea spectabilis; paper flower; phytochemical substance; plant